Phytohormone and Putative Defense Gene Expression Differentiates the Response of ‘Hayward’ Kiwifruit to Psa and Pfm Infections - Wurms, Kirstin V.; Hardaker, Allan J.; Ah Chee, Annette; Bowen, Judith; Phipps, Janet; Taylor, Joseph; Jensen, Dwayne; Cooney, Janine; Wohlers, Mark; Reglinski, Tony (Frontiers in Plant Science, 2017)
Pseudomonas syringae pv. actinidiae (Psa) and Pseudomonas syringae pv. actinidifoliorum (Pfm) are closely related pathovars infecting kiwifruit, but Psa is considered one of the most important global pathogens, whereas Pfm is not. In this study of Actinidia deliciosa ‘Hayward’ responses to the two pathovars, the objective was to test whether differences in plant defence responses mounted against the two pathovars correlated with the contrasting severity of the symptoms caused by them. Results showed that Psa infections were always more severe than Pfm infections, and were associated with highly-localised, differential expression of phytohormones and putative defence gene transcripts in stem tissue closest to the inoculation site. Phytohormone concentrations of jasmonic acid (JA), jasmonate isoleucine (JA-Ile), salicylic-acid (SA) and abscisic acid (ABA) were always greater in stem tissue than in leaves, and leaf phytohormones were not affected by pathogen inoculation. Pfm inoculation induced a 3-fold increase in SA in stems relative to Psa inoculation, and a smaller 1.6-fold induction of JA. Transcript expression showed no effect of inoculation in leaves, but Pfm inoculation resulted in the greatest elevation of the SA marker genes, PR1 and glucan endo-1,3-beta-glucosidase (-1,3-glucosidase) (32 and 25-fold increases respectively) in stem tissue surrounding the inoculation site. Pfm inoculation also produced a stronger response than Psa inoculation in localised stem tissue for the SA marker gene PR6, jasmonoyl-isoleucine-12-hydrolase (JIH1), which acts as a negative marker of the JA pathway, and APETALA2/Ethylene response factor 2 transcription factor (AP2 ERF2), which is involved in JA/SA crosstalk.WRKY40 transcription factor (a SA marker) was induced equally in stems by wounding (mock inoculation) and pathovar inoculation. Taken together, these results suggest that the host appears to mount a stronger, localised, SA-based defence response to Pfm than Psa.